INDIAN TELEVISION ADVERTISEMENTS: SELLING AND SAILING ALTERNATIVE NON-STEREOTYPED DISCOURSE - Mandal, Tapan (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Advertising is an audio-visual form of cultural artifact that not only seeks to generate increased consumption of their products or services through ‘branding’ and ‘standardization’ of the products but also passes some normative ideas, standardized social values and symbolic meaning to the consumers. So, it has a dialogic and reciprocal relationship with other cultural institutions like family, religion, arts, literature and music, which reflects, shapes, and naturalizes consumers’ sense of social reality. Therefore, advertisements act as a political agency to validate and promote established social values and norms like hetero-normative sexuality, docile womanhood, conventional marriage within the structure of patriarchy. But, on the other hand it is noticeable that some television advertising such as "Vicks - New generation for Care", Ads of Mintra, New Biba ad, "Havells Fans- Hawa Badlegi," Rebtel ad, Virgin mobile ad, "Knorr- One night with Karan", and few non-commercial ads such as ad on UN human rights, "Independence Day-#Free the roads", "The seatbelt crew case" covertly as well as overtly subvert the stereotypical social construction of gender and sexuality, motherhood, womanhood and also scaffold an alternative space for the so far "silenced", suppressed, and neglected.